Climate law in European Union legislation. Does it already exist? - Szyrski, Mariusz (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2023)
In July 2021, Regulation (EU) 2021/1119 of the European Parliament and of the Council on the establishment of a framework for achieving climate neutrality entered into force. In this context, it is therefore important to determine whether a conceptual category such as ‘climate law’ can indeed be distinguished in EU legislation and, if so, what is the meaning of this notion? To this end, the notion of ‘European climate law’ is analysed. The dogmatic-legal method is primarily used as the research method in this study. A theoretical-legal method is also used to highlight certain themes related to legal institutions. The research is narrowed down to selected normative acts that are part of the EU legislation – the provisions of normative acts related to the functioning of the EU are analysed. The main conclusions in the paper focus on the application of the term ‘climate law’ in the selected EU regulations. This is juxtaposed with the category of the legal system sensu stricto and sensu largo. The analysis carried out confirms the thesis that Regulation (EU) 2021/1119 of the European Parliament and of the Council of 30 June 2021 on the establishment of a framework for achieving climate neutrality should be classified as climate law sensu largo.